2021
DOI: 10.1186/s12967-021-02735-3
|View full text |Cite
|
Sign up to set email alerts
|

Biomarker profiling for risk of future heart failure (HFpEF) development

Abstract: Background The purpose of this study was to investigate the utility of BNP, hsTroponin-I, interleukin-6, sST2, and galectin-3 in predicting the future development of new onset heart failure with preserved ejection fraction (HFpEF) in asymptomatic patients at-risk for HF. Methods This is a retrospective analysis of the longitudinal STOP-HF study of thirty patients who developed HFpEF matched to a cohort that did not develop HFpEF (n = 60) over a sim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 45 publications
0
24
0
3
Order By: Relevance
“…Whilst exogenous hormone therapy in post-menopausal women is not beneficial for primary prevention, measuring endogenous hormone levels could be useful for risk stratification especially in populations known to have more androgenic profiles like in polycystic ovarian syndrome. In addition, there is evidence to also support the use of hsTroponin I alongside BNP in predicting new-onset HFpEF with similar reported effects in men and women [29,30]. Once risk of HFpEF is established, the same study also found that galectin-3 measurements could help monitor its progression over time.…”
Section: Biomarkersmentioning
confidence: 76%
“…Whilst exogenous hormone therapy in post-menopausal women is not beneficial for primary prevention, measuring endogenous hormone levels could be useful for risk stratification especially in populations known to have more androgenic profiles like in polycystic ovarian syndrome. In addition, there is evidence to also support the use of hsTroponin I alongside BNP in predicting new-onset HFpEF with similar reported effects in men and women [29,30]. Once risk of HFpEF is established, the same study also found that galectin-3 measurements could help monitor its progression over time.…”
Section: Biomarkersmentioning
confidence: 76%
“…To measure galectin-3 concentration in circulation, three studies (6,7,15) used Abbot Laboratories' Architect System, one study (12) used a human galectin-3 assay kit , another (2) used a Quantikine USA kit, and the rest all used enzyme-linked immunosorbent assays (ELISAs) from various manufacturers. Detailed galectin-3 measurement information, including storage temperature and storage duration (where provided), is shown in Table 4.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the association between SLPI and HF was driven by incident HFpEF but not HFrEF upon subgroup analysis. This differential association is notable because while many circulating proteins are associated with incident HFrEF, there are very few specific for incident HFpEF [23][24][25][26][27][28] . The SLPI-HFpEF association is also in accordance with the different contributions of inflammation to the pathophysiology of HFpEF as compared with HFrEF 29 .…”
Section: Discussionmentioning
confidence: 99%